System, Human Resource Developme DESIGN AND DEVELOPMENT OF WEBSITE-BASED HR TRAINING AND HR DEVELOPMENT SERVICES INFORMATION SYSTEM (CASE STUDY OF CV BOENGKAR NUSANTARA JAYA): DESIGN AND DEVELOPMENT OF WEBSITE-BASED HR TRAINING AND HR DEVELOPMENT SERVICES INFORMATION SYSTEM (CASE STUDY OF CV BOENGKAR NUSANTARA JAYA) - Wahyuni, Sri; Farida Yusuf; Alqi, Halqi Safri (Jurnal INSYPRO (Information System and Processing), 2022)
This research is motivated by HR training and development consulting services. The problem faced by CV Boengkar Nusantara Jaya is the ineffectiveness in disseminating information because it is still in the form of brochures to distribute to agencies and companies so that this institution takes quite a long time to process activities because it has to hold meetings repeatedly. The next problem is that it is difficult for customers to know the location of activities and frequent schedule collisions with other customers due to lack of information on activity locations and lack of information on activity schedules. The type of research carried out is qualitative research and the methods used to obtain data are observation, interviews, literature studies, and questionnaires The waterfall method is the application design methodology used in this study. The black box testing approach is used in system testing.